If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14x + -1(-5x) + 31 + -1(-25) + -7x = 0 Remove parenthesis around (-5x) 14x + -1 * -5x + 31 + -1(-25) + -7x = 0 Multiply -1 * -5 14x + 5x + 31 + -1(-25) + -7x = 0 Multiply -1 * -25 14x + 5x + 31 + 25 + -7x = 0 Reorder the terms: 31 + 25 + 14x + 5x + -7x = 0 Combine like terms: 31 + 25 = 56 56 + 14x + 5x + -7x = 0 Combine like terms: 14x + 5x = 19x 56 + 19x + -7x = 0 Combine like terms: 19x + -7x = 12x 56 + 12x = 0 Solving 56 + 12x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-56' to each side of the equation. 56 + -56 + 12x = 0 + -56 Combine like terms: 56 + -56 = 0 0 + 12x = 0 + -56 12x = 0 + -56 Combine like terms: 0 + -56 = -56 12x = -56 Divide each side by '12'. x = -4.666666667 Simplifying x = -4.666666667
| 4y+3=5x-4 | | 0.2n=40 | | X-X*0.16= | | 60t-15t^2=0 | | 3xsqare+10x+12=0 | | (x+3)=25 | | 4x^2-2ox=11 | | 3/10x-3/5x=-15 | | 3/10-3/5 | | 4(x+1)sqare=3x-1 | | 9x+10=45+x | | 5x+22=13x-72 | | (10y^5)-(15y^4)-(25y^3)=0 | | 5xy(2xy-3)= | | (6X-1)(-5-4X)= | | 4x(5x+2x-7)= | | 59-4x=23x+17 | | (4x+5)(-7X+4)= | | 2x^2+x+5=1 | | 8x-41=6x-9 | | 4x-15=7(2x-3) | | (x+1/2)(2x-1/3) | | 3(x-2)=5x+12 | | 2cx+4dx= | | 3/1-1/3 | | 3-1/3 | | x^3-4=3 | | 4x^2-21x+42=6x+7 | | x^2+12x+21=3x+3 | | X*(4/100)+X=205 | | 2y^2+y=-11y | | x^2-11x-1=0 |